2013
DOI: 10.1093/cercor/bht257
|View full text |Cite
|
Sign up to set email alerts
|

Listener-Speaker Perceived Distance Predicts the Degree of Motor Contribution to Speech Perception

Abstract: Listening speech sounds activates motor and premotor areas in addition to temporal and parietal brain regions. These activations are somatotopically localized according to the effectors recruited in the production of particular phonemes. Previous work demonstrated that transcranial magnetic stimulation (TMS) of speech motor centers somatotopically altered speech perception, suggesting a role for the motor system. However, these effects seemed to occur only under adverse listening conditions, suggesting that de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 47 publications
(62 reference statements)
4
35
0
Order By: Relevance
“…Importantly, however, we also present data that go beyond the observation of group effects, as we highlight how the relationship between motor activation and perception may operate on an individual level, complementing previously observed relationships between behaviour and the speech motor system (Bartoli et al, 2015;D'Ausilio et al, 2014). Here, we found that individuals were highly varied in their ability to identify distorted speech sounds and that this corresponded to the level of activity in their speech motor system during speech perception.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Importantly, however, we also present data that go beyond the observation of group effects, as we highlight how the relationship between motor activation and perception may operate on an individual level, complementing previously observed relationships between behaviour and the speech motor system (Bartoli et al, 2015;D'Ausilio et al, 2014). Here, we found that individuals were highly varied in their ability to identify distorted speech sounds and that this corresponded to the level of activity in their speech motor system during speech perception.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, the presence of somatotopic facilitation during distorted speech findings that have shown somatotopic TMS effects reflected in differences in behavioural performance when using non-distorted speech (Bartoli et al, 2015;Möttönen and Watkins, 2009). The high degree of stimulus predictability and certainty, and/or lack of an active listening task to moderate stimulus engagement may have resulted in the absence of somatotopic effects during perception of natural speech, and modulation of the motor system more generally (Hickok et al, 2011;Möttönen and Watkins, 2009;Sato et al, 2009).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The motor cortex, especially the left motor cortex, plays an active role in speech perception, as it is involved in the discrimination of speech sounds (Bartoli et al, 2013;Osnes et al, 2011). This left motor system seems to contribute to speech perception under adverse listening conditions, such as under conditions of degraded or incomplete speech but with recognizable phonetic signals (Osnes et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, it has been proposed that the rolandic alpha ERD reflects the unspecific activation of sensorimotor areas, while the beta ERD signals a relatively more focal motor recruitment (Pfurtscheller & Da Silva, 1999;Pfurtscheller, Pregenzer, & Neuper, 1994). In fact, specific sensorimotor regions recruited during speech production are also activated during speech listening (Fadiga, Craighero, Buccino, & Rizzolatti, 2002;Watkins et al, 2003;D'Ausilio et al, 2014) and the perturbation of these sensorimotor centers affects speech discrimination performance (Meister, Wilson, Deblieck, Wu, & Iacoboni, 2007;D'Ausilio et al, 2009;D'Ausilio, Bufalari, Salmas, & Fadiga, 2012;Bartoli et al, 2015;Möttönen & Watkins, 2009). In fact, specific sensorimotor regions recruited during speech production are also activated during speech listening (Fadiga, Craighero, Buccino, & Rizzolatti, 2002;Watkins et al, 2003;D'Ausilio et al, 2014) and the perturbation of these sensorimotor centers affects speech discrimination performance (Meister, Wilson, Deblieck, Wu, & Iacoboni, 2007;D'Ausilio et al, 2009;D'Ausilio, Bufalari, Salmas, & Fadiga, 2012;Bartoli et al, 2015;Möttönen & Watkins, 2009).…”
Section: Discussionmentioning
confidence: 99%